The Relationship between Factors Influencing Technopreneurs and Technopreneur Intention among Bachelor of Technology Students at FPTV - MUHAMMAD, NURUL AQILAH; Norhasyimah Hamzah (Research and Innovation in Technical and Vocational Education and Training, 2025)
Technopreneurship is a strategic approach in the nation's economic development that emphasises technological innovation in the digital and technological era. However, the lack of student involvement in the field of technopreneurship has become a concerning issue. Therefore, this study was conducted to identify the relationship between factors influencing technopreneurship namely computer ability, internet ability, entrepreneurial orientation, entrepreneurial experience and access to capital, and technopreneurial intention among Bachelor of Technology (BTECH) students at the Faculty of Technical and Vocational Education (FPTV), Universiti Tun Hussein Onn Malaysia (UTHM). This study employed a survey design with a quantitative approach involving 146 BTECH students from Cohort 4 covering seven academic programmes as respondents through full sampling method. Data were analysed using the Statistical Package for the Social Sciences (SPSS) version 27 through descriptive analysis using mean scores and standard deviation as well as inferential analysis using Spearman's rho correlation. Descriptive analysis findings showed that students' levels of computer ability, internet ability and entrepreneurial experience were high, while the levels of entrepreneurial orientation, access to capital and technopreneurial intention were moderate. Inferential analysis revealed a significant relationship between all five factors influencing technopreneurship and technopreneurial intention. This study found that all the involved factors play a crucial role in encouraging students towards a career as technopreneurs.